2020
DOI: 10.3390/atmos11091000
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Hidden Markov Bayesian Classifier and Propagation Concept for Probabilistic Assessment of Meteorological and Hydrological Droughts in South Korea

Abstract: Drought is one of the most destructive natural hazards and results in negative effects on the environment, agriculture, economics, and society. A meteorological drought originates from atmospheric components, while a hydrological drought is influenced by properties of the hydrological cycle and generally induced by a continuous meteorological drought. Several studies have attempted to explain the cross dependencies between meteorological and hydrological droughts. However, these previous studies did not consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 45 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…The results revealed that ANN (coefficient of determination: R 2 = 0.86) outperformed SVR (R 2 = 0.75) in anticipating temporal drought trends. Sattar et al [16] evaluated the hydrological and meteorological droughts using the Markov Bayesian classifier model. The model was 36 to 76% accurate in predicting meteorological drought, whereas it was 33 to 70% accurate in predicting hydrological drought.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that ANN (coefficient of determination: R 2 = 0.86) outperformed SVR (R 2 = 0.75) in anticipating temporal drought trends. Sattar et al [16] evaluated the hydrological and meteorological droughts using the Markov Bayesian classifier model. The model was 36 to 76% accurate in predicting meteorological drought, whereas it was 33 to 70% accurate in predicting hydrological drought.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, drought can be categorized as meteorological, hydrological, agricultural, and socio-economic drought. erefore, it requires the investigator to consider individual opinions to define a specific type of drought [1,2,7,8].…”
Section: Introductionmentioning
confidence: 99%